Merger and Its Implications for Employee Motivation and Productivity at Bank Syariah Indonesia - Mohammad Zeylo Auriza; Erwan Sastrawan Farid; Mohammad Ega Nugraha; Muhammad Riswandi Palawa; Setiawan Mandala Putra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze merger and its implications for employee motivation and productivity at Bank Syariah Indonesia. The type of research used is explanatory research. The research is conducted at Bank Syariah Indonesia in Palu City Area, the respondents in this study are employees of Bank Syariah Indonesia in Palu City. The sampling technique used by the author is non-probability sampling. The type of non-probability sampling used in this study is saturated sampling or often called census. So, the sample in this study is the entire population taken, namely all employees of Bank Syariah Indonesia Palu Area, totaling 126 employees. Data analysis in this study uses structural equation modeling through path analysis. The results show that merger has a significant effect on employee motivation at Bank Syariah Indonesia. Merger has a significant effect on productivity at Bank Syariah Indonesia. Motivation has a significant effect on productivity at Bank Syariah Indonesia.